Zhodnocení hospodaření vybraného kraje - Prokschová, Annette (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalářská práce „Zhodnocení hospodaření vybraného kraje“ se zabývá problematikou hospodaření Jihomoravského kraje v letech 2011-2015. První část obsahuje teoretická východiska práce. V analytické části je představen Jihomoravský kraj a analýza příjmů a výdajů. V poslední části jsou navržena opatření na zlepšení hospodaření tohoto kraje.

The bachelor's thesis "Evaluation of the Economy of a Selected Region" deals with the management of the South Moravian Region in 2011-2015. The first part contains basic concepts. The analytical part presents the South Moravian Region and an analysis of revenues and expenditures. The last part proposes measures to improve the economy of this region.
Evaluation of the Economy of the Selected Region
Keywords: veřejné finance; kraj; Jihomoravský kraj; hospodaření kraje; rozpočet; příjmy; výdaje; public finances; region; South Moravian Region; economy of region; budget; revenues; expenditures